PTU-037 Fontan associated liver disease – early experience and insights from liver screening. Issue 2 (June 2019) - Heng, Ee Ling; Lim, Joanna CE; Abraham, Dilip; Alam, Mohammed; Chung, Natali AY; Emmanuel, Yaso; Frigiola, Alessandra; Head, Catherine E; Tritto, Giovanni
Abstract : Introduction: There is growing recognition of Fontan-associated liver disease (FALD), which encompasses a spectrum ranging from liver congestion to cirrhosis and hepatocellular carcinoma. Diagnostic pathways remain poorly defined, with no consensus on optimal screening and management modalities. Aim of this study was to assess prevalence and severity of FALD by implementation of a structured screening programme. Methods: A cohort of 93 Fontan patients aged ≥ 16 years underwent a screening protocol for liver disease at our tertiary Adult Congenital Heart Disease Centre, including blood tests, liver ultrasound with elastography, and fibroscan. Results were discussed in a MDM and patients categorised according to the risk of having liver fibrosis. MRI, CT scan and/or endoscopy were also organised when appropriate. Patients were followed up yearly if the initial tests were reassuring, or started on 6-montly HCC surveillance if the initial screening suggested advanced fibrosis. Results: The study cohort comprised 55 (59%) males, mean age 25.4±6.2 years, and median 18 years since Fontan surgery. Most patients were asymptomatic (79%), with good haemodynamics. Liver abnormalities on ultrasonography were evident in 51% (41 of 80 scans), including coarse echotexture (41%), hepatomegaly (12%), hyper-echoic nodules (6%) and signs of portal hypertension (15%). Liver stiffness was elevated on both ultrasound elastography (mean 7.8±3.3 kPa, Philips US ElasPQ) and fibroscan (median 20.0±6.7 kPa). Liver MRIs and triple phase liver CTs, performed in a subset of the cohort, further characterised liver abnormalities, most notably focal nodular hyperplasia (FNH) in 65% (13 of 20 MRIs). Most patients had normal biochemical liver profiles, with mean values for bilirubin 18.2 ± 10.6umol/L, ALT 26.5 ± 10.6IU/L, albumin 47.5 ± 5.3g/L and platelets 169 ±55 x10 9, despite hepatic imaging of parenchymal abnormalities. Two patients were found to have hepatocellular carcinomas (HCC), BCLC stage B and C at diagnosis. There was a total of 4 deaths over a median follow-up of 2.8 years, of which 2 deaths were liver-related. Conclusions: Elevated hepatic stiffness and ultrasound appearance in keeping with severe fibrosis are common in adult Fontan patients, despite normal liver enzymes and synthetic function. FNH is the most common abnormality on imaging in high risk patients. The incidence of HCC justifies surveillance in this group of patients, however the optimal surveillance protocol remains to be established.